Status and prospects of yam somatic embryogenesis: a pathway for biotechnology applications - Ossai, C.O.; Balogun, M.O.; Maroya, N.G. (2025)
Yam is an important staple in sub-Saharan Africa, but the availability of quality seed yam is majorly constrained by the low propagation ratio. This is because the propagating explant is limited to the tuber and nodal parts as yam rarely flowers. There are several reports of the use of somatic embryogenesis (SE) in the rapid propagation of different crop species and as a regenerative pathway in plant genetic engineering. However, SE deployment in yam is still at the protocol development stage. This review thus exploits the status of SE application in improving the yam propagation rate. This article reviews the potential of the various yam propagation techniques in rapidly multiplying disease-free yam with their propagating explants. The advantages SE offers are rapidly propagating yam, the factors to consider in the protocol optimization of SE application in rapidly multiplying different yam varieties, and as a platform for full utilization of genetic engineering in yam. The findings so far show that SE potentially offers a faster rate of propagating yam varieties. However, due to the differences in varietal endogenous hormonal and gene products, response to SE in yam is constrained by varietal specificity. Hence, the applicability of SE in yam is still at the protocol development state. This review, thus, presents the need for more research efforts to elucidate the molecular and phytochemical controlling mechanisms of SE in yam to improve the yam multiplication rate and lay an efficient platform for the exploitation of other biotechnological advancements in improving yam species.